Cyclostationarity: Theory and Methods III Contributions to the 9th Workshop on Cyclostationary Systems and Their Applications, Grodek, Poland, 2016 - Chaari, Fakher; Leskow, Jacek; Napolitano, Antonio; Zimroz, Radoslaw; Wylomanska, Agnieszka (Applied Condition Monitoring,, 2017)
This book gathers contributions presented at the 9th Workshop on Cyclostationary Systems and Their Applications, held in Gródek nad Dunajcem, Poland in February 2016. It includes both theory-oriented and practice-oriented chapters. The former focus on heavy-tailed time series and processes, PAR models, rational spectra for PARMA processes, covariance invariant analysis, change point problems, and subsampling for time series, as well as the fraction-of-time approach, GARMA models and weak dependence. In turn, the latter report on case studies of various mechanical systems, and on stochastic and statistical methods, especially in the context of damage detection. The book provides students, researchers and professionals with a timely guide to cyclostationary systems, nonstationary processes and relevant engineering applications.